Old Philadelphia Houses on Society Hill, 1750–1840 - McCall, Elizabeth B. (Rowman & Littlefield Publishers, 2014)
Officially known as Washington Square Park, Philadelphia’s Society Hill district contains an impressive number of eighteenth- and early nineteenth-century houses—perhaps as many as any other comparable area in the United States. This book presents, in text and pictures, the stories of its outstanding Colonial and Early American mansions and dwellings and simple row houses; its churches and other exceptional historic buildings. Old Philadelphia Houseson Society Hill contains both notes and illustrations on the design and architectural details of early Philadelphia row houses. There are also enlightening chapters devoted to such famous places as Bell’s Court, the Drinker House and Drinker’s Court, the Head House and Old Market, the Hill-Physick-Keith House and the Latta House, Old Pine Street Church and the Pennsylvania Hospital, the Man Full of Trouble Inn and many others, all complemented by photos. Featured are the uses of brick and the traditional design and decoration of the period’s interiors, showing antique furniture and prevailing modes of interior decoration. The 150 photographs strike a nice balance of exteriors and interiors, showing characteristic basics and details of structure and charming furniture pieces and accessories of old-time daily living. Tidbits of information concerning such personages as George Washington, Benjamin Franklin, Dr. Benjamin Rush and other eminent Americans are scattered throughout the book.